Impact of organizational creativity climate on employee’s innovative behaviors: Evidence from Vietnam - Nguyễn, Thị Huyền (2020)
Innovation is the key for organizations to maintain their competitive advantages in the world of growing competition. The employees are individuals who creates and implements these innovations and innovative behaviors of employees have been asserted to have a significant impact on work outcomes and organizational innovation performance. Interested in understanding effects of environmental factors on employee’s innovative behavior, this research adopted an 8-dimensional model from Amabile (1996) and 4-dimensional innovative behavior from De Jong and Den Hartog (2010) to test the relationship between them. Moreover, as there are very limited in innovative behavior are conducted in Vietnam, this research hopes to contribute to literature about creativity climate and innovative behavior in Vietnam